HPV Prevalence and Detection of Rare HPV Genotypes in Hong Kong Women from Southern China with Cytological Abnormalities. (17th December 2013) - Co, Ngai Na Chloe; Chu, Lai-On; Chow, Joseph K. F.; Tam, Joseph W. O.; Ng, Enders K. O.
Abstract : Human papillomavirus (HPV) has been identified as the primary cause of cervical squamous intraepithelial lesion and invasive cervical cancer. The emergence of various commercial HPV genotyping kits with different characteristics facilitates the detection of most high-risk and low-risk HPV genotypes, but the rare HPV types are usually underdiagnosed. In the present study, HPV detection was performed using the GenoFlow HPV Array Test kit (DiagCor Bioscience), which can identify 33 HPV subtypes by specific probes. Besides, a HPV consensus probe (universal probe) was designed to capture not only the 33 genotypes but also rare subtypes. Of the 1643 Southern Chinese women tested between 2012 and 2013, the HPV prevalence was 42.3%, with HPV 52 (139/1643, 8.5%), HPV 81 (89/1643, 5.4%), and HPV 16 (63/1643, 3.8%) being the most frequent subtypes detected. Among all 695 HPV-positive cases, 56 (8.1%) cases were only detected by the universal probe, in which 5 were either ASCUS or LSIL cases. Sequencing results confirmed HPV types 30, 91, and 74, and the intratypic variants of HPV 72 and 82 were present in the 5 cases. The result suggests that some rare HPV subtypes might be involved in cervical lesions.